2022
DOI: 10.1007/s13730-022-00695-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of IgA vasculitis with severe glomerulonephritis after COVID-19 vaccination: a case report and literature review

Abstract: With the worldwide spread of the COVID-19 vaccine program during the COVID-19 pandemic, the numbers of reported cases with new-onset or relapsed kidney disease/vasculitis such as minimal change nephrotic syndrome, immunoglobulinA (IgA) nephropathy, and IgA vasculitis (IgAV) that developed after COVID-19 vaccination are increasing. We present the case of a 67-year-old Japanese woman who developed IgAV with purpura on her extremities and trunk in the evening of the day that she received the second dose of the Pf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
(55 reference statements)
2
14
0
4
Order By: Relevance
“…Baseline digestive and renal involvement were rare in our cohort, representing 33% and 17% of the cases. Of note, both in our study and in the literature, no life-threatening organ involvement was observed, with the exception of one patient, in literature, who presented with renal involvement during the course of IgAV requiring cyclophosphamide (19).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Baseline digestive and renal involvement were rare in our cohort, representing 33% and 17% of the cases. Of note, both in our study and in the literature, no life-threatening organ involvement was observed, with the exception of one patient, in literature, who presented with renal involvement during the course of IgAV requiring cyclophosphamide (19).…”
Section: Discussionsupporting
confidence: 58%
“…Hereby, we report the first case series including 12 patients who presented with IgAV following vaccination against COVID-19, providing similar data on both presentation and outcome regarding IgAV of other aetiology (18). So far, reports of IgAV following vaccination against COVID-19 were scarce (19). Of the 11 cases reported in adults, 9 were new onset vasculitis following vaccination and 2 were relapses of one previously proven and one presumed IgAV.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…They showed hematuria but did not present with proteinuria or significantly decreased renal function. The 20-40 mg/day of prednisolone or methylprednisolone was prescribed to the patients; two of them showed complete remission, and the data concerning the prognosis of the third patient was not available [12]. These documented cases suggest that the development of IgA vasculitis after COVID-19 vaccination is not limited to coincidence, and that the vaccines have the potential to trigger IgA vasculitis.…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between these occurrences of IgA vasculitis following vaccination against COVID-19 dominantly favors correlation rather than coincidence, based on other cases which have been recently reported. There have been increasing reports of cases of IgA vasculitis that occurred after COVID-19 vaccination [7][8][9][10][11][12]. Table 2 summarizes the cases of new-onset or relapsed IgA vasculitis following COVID-19 vaccination by conducting a searching of the Pubmed as of 31 May 2022.…”
Section: Discussionmentioning
confidence: 99%